Lead exposure and antisocial behavior: A systematic review protocol. (October 2022) - Shaffer, Rachel M.; Forsyth, Jenna E.; Ferraro, Greg; Till, Christine; Carlson, Laura M.; Hester, Kirstin; Haddock, Amanda; Strawbridge, Jenna; Lanfear, Charles C.; Hu, Howard; Kirrane, Ellen
Abstract: Background: Lead exposure remains highly prevalent worldwide despite decades of research highlighting its link to numerous adverse health outcomes. In addition to well-documented effects on cognition, there is growing evidence of an association with antisocial behavior, including aggression, conduct problems, and crime. An updated systematic review on this topic, incorporating study evaluation and a developmental perspective on the outcome, can advance the state of the science on lead and inform global policy interventions to reduce exposure. Objectives: We aim to evaluate the link between lead exposure and antisocial behavior. This association will be investigated via a systematic review of human epidemiological and experimental nonhuman mammalian studies. Methods: The systematic review protocol presented in this publication is informed by recommendations for the conduct of systematic reviews in toxicology and environmental health research (COSTER) and follows the study evaluation approach put forth by the U.S. EPA Integrated Risk Information System (IRIS) program. Data sources: We will search the following electronic databases for relevant literature: PubMed, BIOSIS and Web of Science. Search results will be stored in EPA's Health and Environmental Research Online (HERO) database. Study eligibility and criteria: Eligible human epidemiological studies will include those evaluating any population exposed to lead at any lifestage via ingestion or inhalation exposure and considering an outcome of antisocial behavior based on any of the following criteria: psychiatric diagnoses (e.g., oppositional defiant disorder (ODD), conduct disorder (CD), disruptive behavior disorders (DBD)); violation of social norms (e.g., delinquency, criminality); and aggression. Eligible experimental animal studies will include those evaluating nonhuman mammalian studies exposed to lead via ingestion, inhalation, or injection exposure during any lifestage. The following outcomes will be considered relevant: aggression; antisocial behavior; and altered fear, anxiety, and stress response. Study appraisal and synthesis methods: Screening will be conducted with assistance from an artificial intelligence application. Two independent reviewers for each data stream (human, animal) will screen studies with highest predicted relevance against pre-specified inclusion criteria at the title/abstract and full-text level. Study evaluation will be conducted using methods adapted from the U.S. EPA IRIS program. After data extraction, we will conduct a narrative review and quantitative meta-analysis on the human epidemiological studies as well as a narrative review of the experimental animal studies. We will evaluate the strength of each evidence stream separately and then will develop a summary evidence integration statement based on inference across evidence streams.